FRAUD HEXAGON THEORY ON FRAUDULENT FINANCIAL REPORTING IN TECHNOLOGY SECTOR COMPANIES - Kurnia, Reni Indah; Arum, Enggar Diah Puspa; Tiswiyanti, Wiwik (JURNAL AKUNTANSI FINANCIAL STIE SULTAN AGUNG, 2024)
The study's goal is to investigate the effects of the fraud hexagon, which consists of pressure, opportunity, rationalization, capability, arrogance, and collusion, on financial statement fraud as measured by the F-score model in public sector technology companies listed on the IDX in 2021–2022. The total sampling approach was used to determine the sample. The findings demonstrated that the incidence of fraudulent financial reporting was unaffected by pressure measured by financial targets, opportunities measured by ineffective monitoring, rationalization measured by auditor changes, ability measured by director changes, arrogance measured by the frequency of CEO pictures, and collusion measured by government projects all at the same time. A partially analysis revealed that while collusion has an impact on fraudulent financial reporting, financial targets, inefficient monitoring, rationalization, capability, and arrogance do not. Keywords: Fraud Hexagon, Fraudulent Financial Reporting, F-score Model